The Khufu I Boat: An Empirical Investigation into Its Use - Brier, Bob.
Although the Khufu I Boat is one of the oldest, largest, and best-preserved vessels from antiquity, there has been no empirical experimentation to determine its nautical properties or its function. This paper presents results of the first tank testing of a model of the Khufu I Boat in 1995, and then suggests the vessel’s probable use. doi: http://dx.doi.org/10.5913/jarce.56.2020.a006